Research on the Integration Mechanism of Intangible Cultural Heritage and Ideological-Political Education: An Innovative Practice of Primary School Curriculum Based on Zhuang Ethnic Group’s Xianghuoqiu Study Tour - Huang Yingqiao (Education Research on Study Tours and Practice, 2025)
This study takes Nanxiao Town Central School as a practical case to explore innovative approaches for integrating the intangible cultural heritage of Xianghuoqiu (Fireball Festival) into ideological and political education at the primary school level. By constructing a five -dimensional framework consisting of "Curriculum – Activities – Environment – Faculty – Study Tours," the school developed tiered and progressive school-based teaching materials and experiential learning tasks. This approach shaped a three-step educational model: "Cultural Cognition → Skill Acquisition → Value Internalization." Practice has shown that this model significantly enhances students’ sense of cultural identity and craftsmanship, while also improving teachers’ curriculum development capabilities. The study provides a replicable experience for the deep integration of intangible cultural heritage and ideological education, and it highlights the need to further optimize evaluation systems and digital inheritance methods to ensure the sustainable development of traditional culture in modern education.